Semiconductor photocatalysis to engineering deuterated N-alkyl pharmaceuticals enabled by synergistic activation of water and alkanols - Zhaofei Zhang (Nature Portfolio, 2020)
Controllable deuteration of N-alkyl amines is crucial in drug-development as they constitute over 50% of the top-selling drugs. Here, the authors report a polymeric semiconductor acting as photocatalyst in water-splitting and in isotope alkanol-oxidation by photoexcited electron-hole pairs, and furnishing deuterated amines.